Sex-related outcome of atrial fibrillation ablation: insights from the German Ablation Registry - Zylla, Maura Magdalena; Brachmann, Johannes; Lewalter, Thorsten; Hoffmann, Ellen; Kuck, Karl-Heinz; Andresen, Dietrich; Willems, Stephan; Eckardt, Lars; Tebbenjohanns, Jürgen; Spitzer, Stefan G.; Schumacher, Burghard; Hochadel, Matthias; et al. (Heart rhythm, 2016)
Background Stratification of patients with atrial fibrillation (AF) according to mechanistic and prognostic criteria may optimize the effectiveness and safety of catheter ablation. In women, AF is associated with more severe symptoms and worse prognosis. Objective We sought to assess sex-related differences in catheter ablation procedures and outcome in a large cohort of patients with AF. Methods A total of 3652 patients (1198 women [33%]; 2454 men [67%]) included in the German Ablation Registry were analyzed. Periprocedural parameters and outcome at 12-month follow-up were compared between male and female patients. Results Women were older at the time of ablation (women: 63.6 years; men: 59.1 years; P < .0001) and exhibited a higher prevalence of paroxysmal AF (women: 72%; men: 61%; P < .0001). They were less often affected by cardiovascular disease and reduced left ventricular function. Energy application duration and overall procedure duration were shorter in women. Conversely, the rate of major inhospital complications was increased in female patients (1.9% vs 0.8%; P = .023) and mainly driven by major bleeding events. At follow-up, women experienced higher AF recurrence rates (women: 50%; men: 45%; P = .017) and more often received oral medication for rhythm and rate control. In addition, the rate of pacemaker implantation was higher in the female cohort. Women more frequently reported femoral access site complications (women: 6%; men: 3%; P < .001). Overall, male patients were more often free from AF-related symptoms and satisfied with the treatment. Conclusion Catheter ablation of AF was associated with a distinct sex-related outcome and complication profile that requires consideration in clinical practice.
Gesehen am 14.02.2018